Preservation of Originality in the Translation of Goethe’s Works - Muattar Maqsatullayevna, Mahmudova (International Journal of Psychosocial Rehabilitation, 2020)
Compared to other languages, the translation of German literature into Uzbek began earlier. When Goethe’s translation of the book "Suffering of the Young Werter" was published in German and published in 1975, no major Western European language work in Uzbekistan had been translated from the original. Prior to that, works in other languages, especially those of Western literature were translated into Russian, resulting in mistakes made by the Russian interpreter, along with errors made by the Russian translator.